6)
34, 43, 52, 61, ...
43-34 = 9; 52-43 = 9; 61-52 = 9
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 34
difference: d = 9
so the formula:
![a_n=a+d(n-1)\\\\a_n=34+9(n-1)\\\\a_n = 34+9n-9\\\\\underline{a_n=9n+25}](https://img.qammunity.org/2021/formulas/mathematics/high-school/h07ekzrcke0grehho2gfyl304l5jib9f1t.png)
7)
10, 6, 2, -2, ...
6-10 = -4; 2-6 = -4; -2-2 = -4
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 10
difference: d = -4
so the formula:
![a_n=a+d(n-1)\\\\a_n=10+(-4)(n-1)\\\\a_n = 10-4n+4\\\\\underline{a_n=-4n+14}](https://img.qammunity.org/2021/formulas/mathematics/high-school/lgh23onl4r7v82kv3z0tl18ij0uv08191h.png)
8)
-3, -10, -17, -24, ...
-10-(-3) = -7; -17-(-10) = -7; -24-(-17) = -7
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = -3
difference: d = -7
so the formula:
![a_n=a+d(n-1)\\\\a_n=-3+(-7)(n-1)\\\\a_n =-3-4n+7\\\\\underline{a_n=-7n+4}](https://img.qammunity.org/2021/formulas/mathematics/high-school/cbogeqpz5y8qpmuwym5bnqkydhksxax1nk.png)
9)
7, 8.5, 10, 11.5, ...
8.5-7 = 1.5; 10-8.5 = 1.5; 11.5-10 = 1.5
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 7
difference: d = 1.5
so the formula:
![a_n=a+d(n-1)\\\\a_n=7+1.5(n-1)\\\\a_n =7+1.5n-1.5\\\\\underline{a_n=1.5n+5.5}](https://img.qammunity.org/2021/formulas/mathematics/high-school/9ge4cuvf8e620winpwbc0a3i1tz6afbuv3.png)
10)
30, 22¹/₂, 15, 7¹/₂, ...
22¹/₂-30 = -7¹/₂; 15-22¹/₂ = -7¹/₂; 7¹/₂-15 = -7¹/₂
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 30
difference: d = -7¹/₂
so the formula:
![a_n=a+d(n-1)\\\\a_n=30+(-7\frac12)(n-1)\\\\a_n =30-7\frac12n+7\frac12\\\\ \underline{a_n=-7\frac12n+37\frac12}](https://img.qammunity.org/2021/formulas/mathematics/high-school/gzbenuo1obdmtssadcs9v5a41lp3qgsaio.png)